2011
DOI: 10.1088/0004-637x/731/1/68
|View full text |Cite
|
Sign up to set email alerts
|

Seyfert Galaxies: Nuclear Radio Structure and Unification

Abstract: A radio study of a carefully selected sample of 20 Seyfert galaxies that are matched in orientation-independent parameters, which are measures of intrinsic active galactic nucleus power and host galaxy properties, is presented to test the predictions of the unified scheme hypothesis. Our sample sources have core flux densities greater than 8 mJy at 5 GHz on arcsec scales due to the feasibility requirements. These simultaneous parsec-scale and kiloparsec-scale radio observations reveal (1) that Seyfert 1 and Se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 120 publications
(164 reference statements)
5
46
0
Order By: Relevance
“…The sample is selected such that the two Seyfert subtypes have matched distributions in the orientation-independent properties. We refer readers to see Lal et al (2011) for greater details on the sample selection. The sample was formulated to study the nuclear radio properties of Seyferts and is constrained by the Very Large Baseline Interferometer (VLBI) observing feasibility.…”
Section: The Samplementioning
confidence: 99%
See 3 more Smart Citations
“…The sample is selected such that the two Seyfert subtypes have matched distributions in the orientation-independent properties. We refer readers to see Lal et al (2011) for greater details on the sample selection. The sample was formulated to study the nuclear radio properties of Seyferts and is constrained by the Very Large Baseline Interferometer (VLBI) observing feasibility.…”
Section: The Samplementioning
confidence: 99%
“…Therefore, the samples that have large variations in the AGN and host galaxy properties are expected to show the effect of these variations in the observed properties other than the differences owing to the differing orientations of the obscuring torus. Lal et al (2011) Seyfert sample based on the matched distributions of the orientation-independent parameters, minimizes the impact of differences caused by the differing properties of the AGN as well as host galaxy.…”
Section: The Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Jet Speeds from Multi-epoch VLBI Using VLBI images of a rigorously selected sample of Seyfert galaxies, Lal et al (2004) have shown that the radio properties of the compact parsec-scale features are consistent with the unified scheme for Seyfert galaxies (see Section 1), with no significant evidence for relativistic beaming in their jets (see also Lal et al 2011). Some parsec-scale features in these sources could be termination points of radio jets.…”
Section: Jet Kinematics and Magnetic Field Structurementioning
confidence: 90%